Dynamics and mechanism diffusion in silica liquid: Insight from simulation - Ha, Nguyen Thi Thanh; Bau, Nguyen Quang; Hung, Pham Khac (VNU Journal of Science: Mathematics - Physics; Vol 28 No 1, 2012)
Abstract . In this paper, we numerically study the diffusion mechanism at atomic level in silica liquid via molecular dynamics simulation. The model consisting of 1998 particles and using the BKS potential has been constructed at the temperature from 2600 to 4500 K. Furthermore, we track the evolution of network units with x=4, 5 and 6 over different time. The simulation shows that the diffusivity depends strongly not only on the rate of the exchanging the coordinated oxygens, but also on the correlation effect. This effect is caused by the specific distribution of the exchanging coordinated oxygens (ECO) through the space which leads to spatially heterogeneous dynamics in the liquid. Analyzing the temperature dependence of the correlation coefficient F we found that the slowdown in dynamics near glass transition point is ascribed from percolation of the domains where high frequent exchanging coordinated oxygens occurs.